2009
DOI: 10.2196/jmir.1244
|View full text |Cite
|
Sign up to set email alerts
|

Usability of a Patient Education and Motivation Tool Using Heuristic Evaluation

Abstract: BackgroundComputer-mediated educational applications can provide a self-paced, interactive environment to deliver educational content to individuals about their health condition. These programs have been used to deliver health-related information about a variety of topics, including breast cancer screening, asthma management, and injury prevention. We have designed the Patient Education and Motivation Tool (PEMT), an interactive computer-based educational program based on behavioral, cognitive, and humanistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 12 publications
3
23
0
Order By: Relevance
“…Our results indicated that the heuristics "consistency and standard" and "recognition rather than recall" have the largest number of violations, with the lowest number of violations related to "error prevention" and "Help users recognize, diagnose, and recover from errors" heuristics. These results are similar to the results of other studies, such as the those conducted by Khajouei et al, Atashi et al, and Nabovati et al in Iran (25)(26)(27), and also the studies conducted by Choi and Bakken, Georgsson et al, Joshi et al, and Mirkovic et al in countries other than Iran, which reported a high number of violations concerning these heuristics (28)(29)(30)(31). On the other hand, the unexpected results of this study indicated that the severity of 60.8% of all violations is major and catastrophic, which accounts for more than half of the identified violations and, in this case, and efficiency of the systems, satisfaction of their users, and hospital's financial issues.…”
Section: Discussionsupporting
confidence: 91%
“…Our results indicated that the heuristics "consistency and standard" and "recognition rather than recall" have the largest number of violations, with the lowest number of violations related to "error prevention" and "Help users recognize, diagnose, and recover from errors" heuristics. These results are similar to the results of other studies, such as the those conducted by Khajouei et al, Atashi et al, and Nabovati et al in Iran (25)(26)(27), and also the studies conducted by Choi and Bakken, Georgsson et al, Joshi et al, and Mirkovic et al in countries other than Iran, which reported a high number of violations concerning these heuristics (28)(29)(30)(31). On the other hand, the unexpected results of this study indicated that the severity of 60.8% of all violations is major and catastrophic, which accounts for more than half of the identified violations and, in this case, and efficiency of the systems, satisfaction of their users, and hospital's financial issues.…”
Section: Discussionsupporting
confidence: 91%
“…This would help the user to make a clear distinction between the correct and the incorrect response. This is consistent with literature, where raters using Nielson’s heuristics are able to identify instructions and functionality problems, simplified representation and improved labeling 43. Majority of the violations due to consistency and standards were reported in the self-efficacy assessment module (8%, n = 8), followed by the knowledge module (4%, n = 4) and socio-demographics (1%, n = 1).…”
Section: Discussionsupporting
confidence: 88%
“…Among Hispanic mothers, perceptions of infant rejection to breastfeeding and milk insufficiency are often reported,14 and formula supplementation is practised among one in three mothers 15. Previous research suggests that initiation of breastfeeding may be more frequent among urban women (59%) compared to that among rural women (49%) 16. In urban settings, several longitudinal studies have prospectively examined breastfeeding initiation and discontinuation 17–22.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations